Evolución político-jurídica del problema antártico - Pinochet de la Barra, Oscar (Universidad de Chile. Instituto de Estudios Internacionales, 1981)
A continent without indigenous inhabitants, with a climate not very suitable for human existence, Antarctica has been incorporated into international life thanks to the advancement of science and technology, which suggests the use of its innumerable riches. We are facing a unique case, unprecedented in International Law. In a continent dedicated to peace, without military bases, it is difficult for us to accept the idea that it could be exploited economically. Historical experience indicates that when technically feasible, the southern continent will be exploited. The problem is important, because the Antarctic Treaty does not authorize this economic use, since it was born as a truce of the sovereignty problem, which could precisely be exacerbated by oil extraction and, secondly, because by introducing mining operations in a Special Zone of Conservation of flora and fauna, it will be very difficult not to pollute. Continente sin habitantes autóctonos, con un clima poco apto para la existencia humana, Antártida se ha incorporado a la vida internacional merced al avance de la ciencia y la técnica, lo que hace pensar en el aprovechamiento de sus innumerables riquezas. Estamos frente a un caso único, sin precedentes en el Derecho Internacional. En un continente dedicado a la paz, sin bases militares, nos cuesta aceptar la idea de que este pudiera aprovecharse económicamente. La experiencia histórica indica que cuando sea técnicamente factible, el continente austral será explotado. El problema es importante, porque el Tratado Antártico no autoriza ese aprovechamiento económico, puesto que nació como una tregua del problema de soberanías, que justamente podría verse agudizado por labores petroleras y, segundo, porque al introducir labores mineras en una Zona Especial de Conservación de flora y fauna, será muy difícil no contaminarla.